The Crystal Structure of cis-Dibromotriphenylphosphite Platinum(II) - Javad Sabounchie, Seyyed; Naghipour, Ali (Asian Journal of Chemistry, 2010)
The X-ray crystal structure of cis-dibromotriphenylphosphite platinurn(II), [PtBr2(POPh3)2] has been determined. This complex crystallises in the space group monoclinic, P21/C, with cell constants a = 14.115(4), b = 10.6648(15), c = 23.254(4) Å and v = 3468.2(12) Å3. The Pt-Br1 and Pt-Br2 distances are 2.4739(5) Å and 2.4702 (5) Å which are longer than Pt-P1 and Pt-P2 with 2.2049(11) and 2.2051(11)Å respectively. These data together with bond angles suggest a distorted square-planar geometry for this complex.